Public Perspectives on The Quality of Public Services at The Bailo Village Office - Fatyanur S Parla; Lindanur Sipatu; Rosida Adam; Arie kurniawan (Al-Qalam Institue, 2025)
This study aims to evaluate the quality of public services at the Bailo Village Office, Tojo Una-Una Regency, using a qualitative research approach with a case study design. Data were collected through in-depth interviews with seven informants, including community members and village staff, and through direct observation. This study identified five dimensions of service quality based on the SERVQUAL model, namely reliability, responsiveness, assurance, empathy, and tangibles. The results showed that most services met community expectations, but there remained inequalities in Time efficiency and service speed. The dimensions of reliability and responsiveness were generally good, but some officers were inconsistent in providing efficient service. The dimensions of assurance, empathy, and tangibles also demonstrated good quality, though they still needed improvement, particularly in facility maintenance and the consistency of employee empathy. This study provides recommendations for improving employee training, Time management, and supporting facilities to improve the quality of public services.